2009
DOI: 10.1038/ijo.2009.211
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of childhood overweight and obesity in Australia between 1985 and 2008

Abstract: Background: Popular media, health experts and researchers talk about a paediatric 'obesity epidemic' with exponentially increasing rates of obesity and overweight. However, some recent reports suggest that prevalence may have plateaued. This study examined trends in the prevalence of Australian childhood overweight and obesity since 1985. Specifically, it aimed to determine whether there have been (a) overall increases in average body mass index (BMI), (b) differential patterns of change within age groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
203
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(230 citation statements)
references
References 41 publications
19
203
3
5
Order By: Relevance
“…They showed that the increase in the prevalence of overweight and obesity among Australian children has slowed and plateaued over the past 10 years. Olds et al 1 reported that the findings were consistent with several recent reports from Australia, Sweden, France, the United States and New Zealand. They failed, however, to comment on a unique study conducted on over half a million male adolescents aged 18 years from Sweden.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…They showed that the increase in the prevalence of overweight and obesity among Australian children has slowed and plateaued over the past 10 years. Olds et al 1 reported that the findings were consistent with several recent reports from Australia, Sweden, France, the United States and New Zealand. They failed, however, to comment on a unique study conducted on over half a million male adolescents aged 18 years from Sweden.…”
supporting
confidence: 80%
“…Unfortunately, these interesting analyses have never been replicated, probably because of the fact that the prevalence of morbid obesity in young people is rather low, and consequently large sample sizes are need to address this question. As Olds et al 1 have managed to put together raw data on BMI from 70 758 Australian young people, we encourage the authors to conduct additional analyses to further understand whether the trends reported by Neovius et al 2 are the same in other cohorts. The authors made a first attempt to address this question by examining the mean BMI values within weight-status groups.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly for this analysis, the focus of OPAL is explicitly on increasing the proportion of children aged 0e18 years in a healthy weight range. While Olds et al (2010) has suggested that obesity amongst children has recently plateaued in Australia, it remains at a high level and continues to be a focus. As Evans (2010) notes, focussing on children is key to the pre-emptive paradigm as childhood 'becomes unproblematically associated with the future, because of the affective power of childhood to provoke hope (and by equal measure, fear and tragic loss)' (Kraftl, 2008, p. 84, cited in Evans, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in prevalence of childhood obesity in the 1990s appears to have slowed or reversed in a number of developed countries during the first decade of the 21st century (1)(2)(3) . Data from the Health Survey for England show a rise in the prevalence of obesity in 2-15-year-olds from 11 % in 1995 to 19 % in 2004, followed by a plateau at 15-17 % from 2006 to 2014 (4) .…”
mentioning
confidence: 99%